PENGARUH DANA BAGI HASIL, DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI PROVINSI ACEH - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2019)
This study aims to analyze the effect of profit sharing funds, general allocation funds, and special allocation funds for gross regional domestic products (GRDP) in Aceh Province. The data in this study uses time series data with the 2006-2018 time period sourced from BPS and DJPK. The analytical method used in this study is multiple linear regression using eviews analysis tools. The results showed that general allocation funds and special allocation funds had a positive and significant effect on GRDP, while profit sharing funds had a negative and significant effect on GRDP, then jointly shared revenue funds, general allocation funds, and special allocation funds had a significant effect and positive for GRDP is 0.9871 (89.71%), while those affected by other variables outside of this model are 0.1029 (10.29%).